Radiographic Evaluation of Hip Implants - Chang, Connie Y.; Huang, Ambrose J.; Palmer, William E. (Seminars in Musculoskeletal Radiology, 2015)
Serial radiographs are the mainstay in the longitudinal assessment of hip implants. The prosthesis, periprosthetic bone, and juxta-articular soft tissues are inspected for fracture, periosteal reaction, stress shielding, calcar resorption, osteolysis, bony remodeling, metallic debris, and heterotopic ossification. Comparison radiographs best confirm implant migration, subsidence, and aseptic loosening. Infection, particle disease, reaction to metal, and mechanical impingement are important causes of postsurgical pain, but in their earliest stages they may be difficult to diagnose using radiographs. This article addresses the role of radiography following hip arthroplasty.
Keywords: hip arthroplasty; radiograph; evaluation